Public Opinion Toward Globalization: The Macedonian Experience - Drakulovska Chukaleska, Marija; Dragovikj, Ivana; Dragovikj, Anica (University "Goce Delcev", Shtip, 2017)
Globalization is a phenomenon which, in a great measure, affects every modern society and culture. In the last few decades, in the social sciences, great interest has been taken in this topic, especially in sociology. Sociologists observe this phenomenon as a dynamic process that is built on the base of the mutual connection and dependence between countries and through them explains the changes that happen in the separate sociocultural realities. The theory of globalization refers to the world condensation and intensification of the consciousness of the world as a whole (Robertson, 1992, p. 8). Consciousness has been increasing and the chance for the world to be reproduced as a unique, is growing. That awareness is built on the basis of experience that is a result of the intensification of the world as a whole, and also a consequence of the globalization. In this article our intention is to give analyzes in relation with public opinion for globalization itself in the world, and particularly in Macedonia. Here we will give an observation about the public opinion in relation with this question. On a theoretical level, it analyzes the most significant theories of globalization in sociology, and on an empirical level, through the public opinion, i.e. by measuring the opinions of the public on this phenomenon in Macedonian society. We have researched the opinions of the public through: 1. Respondents’ awareness about globalization; 2. Respondents’ perceptions about the importance of globalization 3. Respondents’ personal opinions on globalization and 4. The presence of globalization worldwide. The research has been conducted on a target sample and has a total of 127 respondents, Macedonian citizens.
Keywords: globalization, awareness, public opinion, changes, Macedonia